The Role of SISKEUDES in Enhancing Accountable and Transparent Village Financial Governance - Selan, Dwi Dersmi (GOVERNORS, 2025)
This study aims to examine the effectiveness of the implementation of the Village Financial System (SISKEUDES) in strengthening village financial governance in Nunmafo Village during the 2022–2024 period. Employing a qualitative descriptive case study approach, data were collected from village officials and SISKEUDES operators through in-depth interviews, direct observation, and document analysis. Primary and secondary data were analyzed using a governance-based effectiveness framework encompassing transparency, accountability, participation, and administrative control. Data validity was ensured through triangulation of interview findings and village financial management documents. The findings indicate that SISKEUDES has contributed positively to improving the accuracy and efficiency of village financial reporting and facilitating financial monitoring processes. However, when assessed against the established effectiveness criteria, the system is categorized as moderately effective due to persistent constraints related to human resource capacity and infrastructure readiness. Limited educational background, insufficient technical training and unstable internet connectivity hinder real-time data processing and optimal system utilization. This study contributes to the existing literature by moving beyond a purely technical evaluation of SISKEUDES and offering a governance-oriented assessment of its effectiveness in a resource-constrained village context. The findings provide practical insights for policymakers and supervisory institutions in designing more context building and infrastructure support strategies to enhance village financial governance